ADHD at school: a study on interaction rituals among students (Práxis Educativa, 2023)
This research aimed to understand how the interaction rituals between a child with Attention Deficit Hyperactivity Disorder (ADHD) and their peers are established in a municipal public school in the area named Médio Vale do Itajaí, Santa Catarina, Brazil. The research, with a qualitative approach, was characterized as a case study based on participant observation of everyday school life and informal conversations with the children of the classroom. The results showed that the interaction rituals are manifested by alliance coalition and conflict. The first, marked by an emotional charge of solidarity among peers, contributes to the child’s sense of belonging to the group and to the school. These interaction rituals, characterized by games, collaborative attitudes and complicity, strengthen the inclusion of children with ADHD in school. Conversely, conflict coalitions, marked by misunderstandings and confrontations, cause the rupture of chains of interactions, leading to feelings of dissatisfaction and exclusion.Keywords: Interaction rituals. School. ADHD.